The formation and training of political cadres for the management of the State in Argentina (2019)
The problem of the formation and training of political cadres for the management of the State constitutes a concern that crosses both theory and political practice, and it is necessary to address it from both perspectives, due to the complexities and challenges that arise when thinking about programs Academics: what competencies do the political cadres require for state management? Where do these instances of education and training have to be developed? How to achieve its concretion and institutionalization? Considering these questions, this work intends to make a contribution to the analysis of state policies aimed at the formation and training of political cadres, since Argentina has failed to stabilize a formative model for such public, as prescribed by the Constitution in its article 38, because the successive efforts have confused the needs and roles of the State with those of the Government, both in the formulation and in the implementation of the policy. The article, first of all, specifies some theoretical conceptions that guide the research and the methodological strategy used. And then, it analyzes the various policies formulated by the Argentine State at different times and under different theoretical-methodological paradigms. The interpretation and understanding of this process constitutes an indispensable contribution in the search for possible solutions to a problem still pending for Argentines: the formation and training of our political class.